Patterns of seedling recruitment in experimental gaps on mosaic vegetation of abandoned meadows - Lidia Borkowska (Acta Societatis Botanicorum Poloniae, 2011)
The paper presents results of a study on the response of species growing in experimental gaps in the patches dominated by Carex acutiformis, C. cespitosa and Salix cinerea. The study was performed in a meadow area subjected to the process of succession in the Reski Range in the Białowieski National Park. Four patterns of seedlings recruitment in the experimental gaps were distinguished: pattern I - great number of seedlings with high richness of species, pattern II - great number of seedlings with low richness of species, pattern III - low number of seedlings with great richness of species and pattern IV - low number of seedlings with low richness of species.